The unique hybrid precipitate in a peak-aged Al-Cu-Mg-Ag alloy. (15th March 2021) - Gazizov, M.R.; Boev, A.O.; Marioara, C.D.; Andersen, S.J.; Holmestad, R.; Kaibyshev, R.O.; Aksyonov, D.A.; Krasnikov, V.S.
Abstract: The prevalent hardening phase forming in an Al-Cu-Mg-Ag alloy after peak-aging at 150 and 190 °C has been investigated using transmission electron microscopy methods. The precipitate atomic structure was determined. It is a hybrid precipitate (HP) with plate morphology on 111Al planes, consisting of orthorhombic and hexagonal structural fragments. Density functional theory calculations suggest that the hybridization reduces structural incompatibility of the HP plates with the Al matrix at the broad interfacial boundaries. Incorporation of Cu, Mg and Ag in the bulk HP structure reduces its formation enthalpy.